Engineered Andrographolide Nanosystems for Smart Recovery in Hepatotoxic Conditions - Roy, Partha; Das, Suvadra; Auddy, Runa Ghosh; Mukherjee, Arup (Dovepress, 2014)
Andrographolide (AG) is one of the most potent labdane diterpenoid-type free radical scavengers available from plant sources. The compound is the principal bioactive component in Andrographis paniculata leaf extracts, and is responsible for anti-inflammatory, anticancer, and immunomodulatory activity. The application of AG in therapeutics, however, is severely constrained, due to its low aqueous solubility, short biological half-life, and poor cellular permeability. Engineered nanoparticles in biodegradable polymer systems were therefore conceived as one solution to aid in further drug-like applications of AG. In this study, a cationic modified poly(lactic-co-glycolic) acid nanosystem was applied for evaluation against experimental mouse hepatotoxic conditions. Biopolymeric nanoparticles of hydrodynamic size of 229.7±17.17 nm and ζ-potential +34.4±1.87 mV facilitated marked restoration in liver functions and oxidative stress markers. Superior dissolution for bioactive AG, hepatic residence, and favorable cytokine regulation in the liver tissues are some of the factors responsible for the newer nanosystemassisted rapid recovery.